MODELING THE DYNAMICS OF SPECIES NUMBERS IN COLLEMBOLA COMMUNITIES - V. G. Soukhovolsky; N. A. Kuznetsova; A. V. Kovalev (Вопросы лесной науки)
The population dynamics of springtails is considered based on long-term surveys. The analysis was performed using data on the total population springtails density of three functional groups. The S group of springtails unites eu- and hemiedaphic forms inhabiting the litter and underlying soil horizons. Springtails of group U include upper litter forms living on the surface of the litter. Group A consists of atmobiontic springtails rising into the ground vegetation cover. For the time series of the dynamics of the number of springtails in each group, ADL (autoregressive distributed lag) models were considered, in which the current population dynamics of springtails was determined as dependent, firstly, on the regulating factors – the number of springtails in three previous counts, and, secondly, on the modifying factor – the accumulated air temperature for three weeks before the date of the count. The proposed model allowed us to describe quite accurately (the determination coefficients R2 for all groups exceeded 0.7) the long-term population dynamics of three functional groups springtails. To assess the stability of the population dynamics of springtails, such an indicator as the stability reserve of the ADL model was calculated and it was shown that the population dynamics of springtails is quite stable and exceeds the stability reserve indicators of forest insect populations.